Pengaruh Penerapan Media Animasi Audio Visual Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPS Kelas IV Di SDN 04 Pedamaran Oki Sumatera Selatan - Resi Relista; Djoko Rohadi Wibowo (Program Studi PGMI, IAI Al-Falah As-Sunniyyah Kencong, 2021)
This study aims to determine student learning outcomes before and after applying audio-visual animation media to social studies subjects for grade IV SDN 04 Pedamaran, and to the effect of applying audio-visual animation media to student learning outcomes in grade IV at SDN 04 Pedamaran. Subjects in this study amounted to 22 students. This study uses a descriptive quantitative method with data collection techniques in the form of; observation, interviews, tests, and documentation. The analysis in this study uses the statistical formula for the